Applications with memory load for lexical activation in foreign language learning - Pichugin, Vitaly; Panfilov, Alexey; Volkova, Elena (Frontiers in Education, 2023)
Investigating effective language learning methods has become increasingly relevant in the modern educational environment. This study aimed to examine the impact of using the mobile applications Duolingo and Memrise on vocabulary expansion, lexical retention, and increasing language confidence among students. A total of 203 students from Kazan Federal University participated in the study and were divided into three groups. Each group was given access to a specific mobile application (Duolingo, Memrise, or traditional teaching methods) for six weeks. The findings indicate that students who used Duolingo demonstrated significantly better outcomes in terms of vocabulary expansion, lexical retention, and increased language confidence compared to the other groups. These results can be valuable for teachers and students aiming to enhance the efficiency of acquiring new language skills. Prospects for further research involve expanding the analysis to include other mobile applications and their influence on the language learning process, as well as considering additional factors. Future studies will provide valuable insights into the influence of mobile applications on language acquisition and identify effective approaches to improve students’ language skills.